1999
DOI: 10.1046/j.1365-2133.1999.02712.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of in-patient dermatology: a survey of in-patients in Scotland and northern England

Abstract: Dermatology in-patient units are frequently threatened with reduction or closure, yet there are few objective data regarding the nature and use of in-patient management with which to assess their value. We have surveyed 300 patients admitted during March 1997 to dermatology units throughout Scotland and Northern England, to establish their clinical and social profile, and the outcome of admission. All departments provided phototherapy and out-patient treatment services, and 84% of those admitted lived within a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
4
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 13 publications
2
47
4
6
Order By: Relevance
“…Seventeen per cent of patients had significant medical problems contributing to the need for admission. This figure is lower than the 43% recorded in the Scottish series 3 possibly because we classified alcohol and psychological problems as ‘social’ rather than medical and we did not include psoriatic arthropathy in our significant medical problems group. Even so most patients did not have medical problems and the use of costly ‘medical’ beds for these patients is arguably not a legitimate expense.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Seventeen per cent of patients had significant medical problems contributing to the need for admission. This figure is lower than the 43% recorded in the Scottish series 3 possibly because we classified alcohol and psychological problems as ‘social’ rather than medical and we did not include psoriatic arthropathy in our significant medical problems group. Even so most patients did not have medical problems and the use of costly ‘medical’ beds for these patients is arguably not a legitimate expense.…”
Section: Discussionmentioning
confidence: 66%
“…This study, amongst few others, 3,4 provides an evidence base for the subjective and objective benefits of inpatient treatment. Importantly patients' quality of life as measured by the DLQI score showed a significant improvement (41.8%) compared with their pre‐admission status.…”
Section: Discussionmentioning
confidence: 85%
“…In these countries the most frequent diagnoses were psoriasis, bullous disorders, chronic ulcers and dermatitis, which represented more than 70% of inpatients. [1][2][3] In Spain surgical patients constituted the majority of inpatients (37%) whereas in Iran bullous disorders constituted around 40% cases. 4,5 Our objectives were to describe inpatient activity in TU Teaching Hospital, a tertiary care centre of Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Yet there undeniably exist several dermatological conditions that are associated with considerable morbidity and mortality . In addition, several studies have demonstrated that inpatient care may be highly effective in facilitating remission in chronic skin diseases, especially in socially disadvantaged patients . Inpatient admission would therefore be justifiable in such patients.…”
Section: Introductionmentioning
confidence: 99%